Harmony and Distress: Humor, Culture, and Psychological Well-Being in South Korean Organizations - Kim, Hee Sun; Plester, Barbara A. (Frontiers in Psychology, 2019)
Humor is a contextual phenomenon that exists in all societies, although the impact of humor may differ across different cultures. The data for this research was collected using an ethnographic approach, incorporating participant observation and semi-structured interviews. Based in three different South Korean organizations, this research offered the opportunity to interact in depth with workers of varying ages, genders, hierarchical levels, and organizational roles. Observations were complimented by 46 in-depth interviews and ad hoc follow-up discussions. This paper adopts a Confucian perspective to understand the perception and use of workplace humor in these South Korean organizations. Confucian philosophy emphasizes the value of formality within society in order to maintain respectful relationships between individuals. We suggest that humor is used in these South Korean workplaces to support traditional Confucian values of harmony and hierarchy, and the changing cultural values in these workplaces influence humor perceptions in complex ways. The Confucian value of harmony maintained through the idea of hierarchy creates pressure for organizational members, to accept and cope with contentious humor in the workplace. In particular, the clash between the need to maintain harmonious relationships in the workplace (through obedience towards superiors) and the desire to reject some types of humor highlights issues for younger organizational members. Internal conflict creates distress for younger employees who may hold more Westernized values and this affects their emotional, psychological well-being. This study presents a cross-cultural perspective to organizational humor, and suggests that humor may not always be a positive experience for organizational members, but instead may create psychological distress in some employees.